Efektivitas Pendekatan Teaching at the Right Level (TaRL) dalam Meningkatkan Kemampuan Menulis Cerpen di Kelas IX-6 SMP Negeri 8 Medan - Zuhra, Fitria Afiatuz; Ali, Ali; Evita, Evita (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the effectiveness of the Teaching at the Right Level (TaRL) approach in enhancing short story writing skills among ninth-grade students at SMP Negeri 8 Medan. Employing a Classroom Action Research (CAR) method implemented in two cycles, the research involved 30 students from Class IX-6. Data were collected through questionnaires, observations, and writing tests, with sources drawn from both students and teachers. The analysis combined quantitative and qualitative descriptive techniques. Initial findings revealed a class mastery level of only 18.3% in the pre-cycle stage. Following the implementation of the TaRL approach, mastery improved to 65.7% in the first cycle and reached 86.4% in the second cycle. These outcomes demonstrate that the TaRL method significantly improves students’ ability to write short stories by aligning instruction with their actual comprehension levels. The approach effectively facilitated idea development, understanding of narrative structure, and enhanced use of language. Furthermore, TaRL fostered greater student engagement by providing personalized and targeted instruction. The study concludes that the TaRL approach is a powerful pedagogical tool for improving creative writing competencies and should be considered for broader application in writing instruction across educational settings.